Análisis comparativo de la gestión del conocimiento y de los modelos más representativos implementados en las PYMES colombianas y chilenas (2021)
Knowledge management is an intangible resource of great value for organizations, this asset allows them to excel, competing with optimal and profitable processes, giving room for innovation, the creation of new products and services. However, the lack of experience of SMEs with respect to knowledge management leads to the waste of this asset, which represents a disadvantage for them, considering the limited resources they have and the fierce competition in the market. The objective of this study is to develop a comparative study of knowledge management and the most representative models applied in Chilean SMEs versus the models proposed in Colombia, with the purpose of adopting those good practices that will allow more SMEs in Colombia to improve the performance in the areas of the organization and optimize the transfer of their knowledge in order to obtain a competitive advantage. The aforementioned problem is answered through the analysis of knowledge management models, which is carried out through the formulation of four descriptors, which are subsequently developed by means of a comparative table and this information is complemented quantitatively through the factor qualification method, where the characteristics and obstacles that both Chilean and Colombian SMEs present in the collection of knowledge management are evaluated. Now, the analysis and study of the subject allows us to deduce that organizations that efficiently manage knowledge will obtain increases in their innovation processes with higher levels of productivity. Even though technology is a springboard to manage knowledge, it should not be an obstacle for SMEs with limited resources, since there are easy access and low cost tools that allow sharing explicit knowledge, always considering as the main input for the success of knowledge management the attitude and commitment of each of the collaborators. Considering this, it is recommended that organizations take into account the particularities of the sector where it is developed, in order to establish a correct collection of the knowledge management model to it. The proposed model must be aligned with the strategic objectives of the organization, also the promotion of the knowledge culture must be permanent with the help of socialization activities to understand and appropriate the strategies and pillars of this.